Chemical, physical, microbiological and sensory analyzes of fillets of hybrid sorubins (Research, Society and Development, 2021)
Sorubim fillets are products with great commercial potential that meet the current preferences for fish consumption. Hybrids of these species have gaining popularity for industrial fish farming. The aim of this work was to characterize fillets obtained from the crosses between Pseudoplatystoma corruscans and Pseudoplatystoma reticulatum (dot and comma hybrid sorubim) and the crosses between Pseudoplatystoma spp. x Leiarius marmoratus (real hybrid sorubim) in terms of physical, chemical, microbiological, and sensory analyzes. The fillets of real hybrid sorubim presented high moisture (77.90%) and protein (17.20%) and low lipid (3.20%) contents compared to the dot and comma hybrid sorubim (75.66, 21.36, and 1.90%, respectively). The variation in the constitution of the real hybrid sorubim had affected other parameters, e.g. it increased the texture evaluated in terms of shear strength (0.58 kgf, against 0.46 kgf for the dot and comma hybrid sorubim fillet), and the reduced sensory acceptation / purchase intention, which are related to the reduced fat content. Purchase intention analysis indicated that the filets of dot and comma hybrid sorubim would be purchased by 95% of the population, while the fillets of the real hybrid sorubim would be purchased for less than 80% of the population.